Modeling and analysis of the effect of thermal losses on thermoelectric generator performance using effective properties. (1st February 2018) - Lee, Heonjoong; Sharp, Jeff; Stokes, David; Pearson, Matthew; Priya, Shashank
Highlights: Modeling captures the contributions from thermal losses and interfacial resistance. The effective properties provide a precise description of the transport properties. Quantification of actual figure-of-merit with thermal losses is performed. The performance of TEG is explained quantitatively through effective properties. The modeling method is applied to various materials to confirm the feasibility. Abstract: A mathematical model for a thermoelectric generator (TEG) based on constitutive equations has been developed to analyze temperature dependent performance in terms of output power and efficiency. Temperature dependent material properties and thermal losses, which occur as conductive and radiative heat transfer, were considered in the finite element model. Effective material properties were invoked for understanding the influence of temperature dependence of material parameters and related adverse effects on the model TEG. It is shown that analytical equations with effective properties can provide excellent estimation of the performance of a TEG over a broad operating range. The model was simulated, analyzed and validated to examine the effects of different operating conditions and geometry that interact with thermal losses inside the TEG. We believe that this model will further expedite the optimization of TEGs being developed using new material compositions.